Endobronchial Ultrasound under Moderate Sedation versus General Anesthesia - Fernandes, MG (2018)
BACKGROUND: Different anesthetic protocols may influence endobronchial ultrasound-guided needle aspiration (EBUS-TBNA) outcomes, patient comfort, and even safety. In this study, two anesthesia techniques were assessed and compared for EBUS-TBNA. METHODS: A prospective, multicenter study was carried out. Patients were allocated to Group 1 (general anesthesia with neuromuscular blockade and controlled ventilation) and Group 2 (intravenous sedation). EBUS-TBNA accuracy was the primary outcome. Safety, patient comfort and satisfaction, and operators' difficulties were defined as secondary outcomes. RESULTS: Of the 115 patients enrolled (Group 1 = 59, Group 2 = 56), EBUS-TBNA was performed for hilar or mediastinal lesion diagnosis and lung cancer staging in, respectively, 77 (67%) and 38 (33%) patients. The numbers of lymph nodes stations (1.8 ± 1.0 vs. 1.7 ± 1.0, p = 0.472) and punctures per station (6.9 ± 3.1 vs. 6.0 ± 2.5, p = 0.084) were similar between groups. Adequate samples were obtained from 109 patients (97.3%) with similar diagnostic accuracy. Procedure duration was not significantly different (p = 0.348). Hemodynamic parameters and systolic and diastolic blood pressures were higher in Group 1 at the beginning and at the end of the procedure. Adverse events were equally distributed, and no significant differences were found regarding patient satisfaction and bronchoscopist/anesthesiologist difficulties. CONCLUSIONS: The type of anesthesia used did not influence EBUS-TBNA outcomes. EBUS-TBNA performed under sedation or general anesthesia did not affect the diagnostic yield, complication rate, and patients' comfort and satisfaction.